Kuwaresma (Bookmark Video and Moving Images, 1998)
Highlights the Lenten rituals of the Philippines through an anthropologist's eye. It shows the different ways Filipinos remember and give life to the passion and death of Jesus Christ. We see the mixing of the old and new, colonial and native traditions, the Catholic Church and the community. Narrated in Filipino.